Uncertainty Avoidance and the Rate of Business Ownership across 22 OECD Countries, 1976-2000 - Sander Wennekers; A. Roy Thurik; André J. van Stel; Niels Noorderhaven (Max Planck Institute for Research into Economic Systems, 2005)
Persistent differences in the level of business ownership across economically developed nations have attracted the attention of scientific as well as political debate. Cultural rather than economic influences are assumed to play a decisive role. This paper deals with the influence of cultural attitudes towards uncertainty on the level of business ownership across OECD countries. First, the concepts of uncertainty and risk are elaborated, as well as their relevance for entrepreneurship. Second, cross-sectional regression analysis using data for three separate years in twenty Western countries and Japan and controlling for GDP per capita, yields evidence that in 1976 and 1988 uncertainty avoidance is positively correlated with the prevalence of business ownership. Possibly, a restrictive climate of large organizations in high uncertainty avoidance countries pushes enterprising individuals towards self-employment. However, in 2000 this positive correlation is no longer found, indicating that a compensating pull mechanism in countries with low uncertainty avoidance may have gained momentum in recent years. Third, we carry out pooled panel regressions with respect to business ownership rates in two distinct cultural country clusters for the years 1976, 1988 and 2000. In the group of high-uncertainty avoidance countries a strongly negative relationship between GDP per capita and the level of business ownership is found, suggesting that rising opportunity costs of entrepreneurship are the dominant perception in this cultural environment. In a group of low-uncertainty avoidance countries no such influence of per capita income is found, but the profits associated with being self-employed are positively associated with business ownership.
Keywords: O11; M13; Z1; P52; O57; 330; business ownership; uncertainty avoidance; cross country study; comparative analysis of economies; cultural economics; entrepreneurship; Unternehmer; Risiko; Wirtschaftssoziologie; Vergleich; OECD-Staaten